Penegakan Hukum atas Pelanggaran Pemanfaatan Sempadan Sungai di Wilayah Kabupaten Sidoarjo - Dwi Prastiandiani (Universitas Muhammadiyah Sidoarjo, 2016)
The purpose of this study to describe and analyze law enforcement in violating the border river in Sidoarjo Regency that in terms of criminal and administrative sanctions. The method used qualitative approach through normative juridical approach. The results showed that the government of Sidoarjo Regency has made several steps in order to control at the Border Wilayut River included coordination offices/agencies, dissemination, data collection, as well as strikes I, strikes II, strikes III from municipal police a period of seven days. Law enforcement in violating the border river in Regency Sidoarjo through administrative sanctions and criminal sanctions. Factors influencing of law enforcement included law factors, facility factors, community factors, as well as cultural factors.